Role of Genetically Modified Microorganisms for Effective Elimination of Heavy Metals. - Misra, Shashi Kiran; Kumar, Ajay; Pathak, Kamla; Kumar, Girish; Virmani, Tarun; Mohammadi, Saeed (BioMed Research International, 2024)
Heavy metals are lethal and hazardous pollutants for the ecosystem owing to their virtues including acute toxicity, prolonged persistence, and bioaccumulation. These contaminants are not only a threat to aquatic/terrestrial biota but also pose serious health issues to humans. Natural and anthropologic processes consistently upsurge heavy metal concentration beyond acceptable limits and mobilization and hence disturb biogeochemical cycles and the food chain, although several conventional strategies including adsorption, chemical precipitation, ion exchange, and membrane separation methods are being employed for the removal of these lethal heavy metals from the ecosystem but failed due to lower efficiency rates and high application charges. The current scenario highly demands advanced biosorption or bioaccumulation processes that slow down heavy metal mobilization within the acceptable limit in the ecosystem. Genetically modified microorganisms (GMMs) with desired features are developed through interdisciplinary participation of genomics, molecular microbiology, and bioinformatics that have more potential to bioremediate heavy metals than the native microbes from polluted ecosystems. The study focuses on different sources of heavy metals, their impact on the ecosystem, and the bioremediation of toxic heavy metals via GMMs.